Huella ecológica en el cultivo de caucho (Hevea brasiliensis), en la zona norte de la provincia de los Ríos, 2018 - Jiménez Cazar, Bismarck Nicolay (2018)
The ecological footprint shows mathematically the current environmental state of the study ecosystems in which man has interfered. The aim of this research is to calculate the ecological footprint in the cultivation of rubber (hevea brasiliensis) in four sectors of the Northern zone of the province of Los Ríos, located in the parishes: Patricia Pilar, El Descanso, La Esperanza y, the Quinsaloma canton. The distance between them was considered and the difference in the frequency of application of inputs to control pests and diseases. The investigation was carried out in the months of August to October of the 2018, the inductive, analytical and exploratory method was applied and the methodologies of determination of biomass (Brown) were used. Necromasa was collected in plots of 25m^2, dehydrated in the soil laboratory of the State Technical University of Quevedo. The ecological footprint was calculated according to Rees & Wackernagel. The results obtained showed that the ecological footprint of the rubber crop in the 4 scenarios showed a level below the accepted global limits, and it is also stressed that these values are lower than those of biocapacity, thus obtaining a surplus Ecological, however, an ecological footprint mitigation Plan was established which will help to maintain and improve the favorable environmental situation. Keywords: Ecological footprint, carbon cycle, Biocapacity, mitigation plan